Subnanomolar dopamine D3 receptor antagonism coupled to moderate D2 affinity results in favourable antipsychotic-like activity in rodent models: II. behavioural characterisation of RG-15 - Gyertyán, István; Sághy, Katalin; Laszy, Judit; Elekes, Ottilia; Kedves, Rita; Gémesi, Larisza I.; Pásztor, Gabriella; Zájer-Balázs, Mária; Kapás, Margit; Ágai Csongor, Éva; Domány, György; Kiss, Béla; et al. (Naunyn-Schmiedeberg's archives of pharmacology, 2008)
RG-15 ( trans -N-{4-[2-[4-(3-cyano-5-trifluoromethyl -phenyl) –piperazine –1 -yl] -ethyl] -cyclohexyl} -3 –pyridinesulfonic amide dihydro-chloride), is a highly selective dopamine D 3 /D 2 receptor antagonist with subnanomolar affinity for the D 3 receptor and nanomolar affinity for the D 2 receptor. We found that RG-15 showed a good oral bioavailability (54%) and high brain levels (approx. 900 ng/g) in rats and demonstrated antipsychotic efficacy in amphetamine-induced hyperactivity and conditioned avoidance response tests in rats, yielding ED 50 (median effective dose) values of 8.6 and 12 mg/kg orally, respectively. At six- to eightfold higher doses, RG-15 blocked spontaneous motor activity, while a 30 mg/kg dose of the compound caused an increase in the home-cage motility of rats. The drug did not produce catalepsy up to 160 mg/kg oral dose; moreover, it inhibited haloperidol-induced catalepsy in the range 15–60 mg/kg. RG-15 (10 mg/kg orally) restored the impaired learning performance of scopolamine- or diazepam-treated rats in a water-labyrinth paradigm. It is assumed that the motor activating, anticataleptic and cognitive-enhancing properties of RG-15 result from its potent D 3 antagonism. In this regard, RG 15 clearly differs from other antipsychotics. Olanzapine, clozapine and amisulpride all showed efficacy against amphetamine-induced hyperactivity and on conditioned avoidance, but compared to RG-15, they proved to be more cataleptogenic and depressed or did not change the home-cage activity of animals. Olanzapine was also inactive in the learning paradigm. Our results suggest that subnanomolar dopamine D 3 receptor antagonism coupled to moderate D 2 affinity may result in an antipsychotic profile characterised by a lack of extrapyramidal side effects and secondary negative symptoms with simultaneous efficacy on positive and cognitive symptoms of schizophrenia.